2012
DOI: 10.1182/blood-2011-12-398438
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular cyclophilin A is an important Ca2+ regulator in platelets and critically involved in arterial thrombus formation

Abstract: Platelet adhesion and aggregation play a critical role in primary hemostasis. Uncontrolled platelet activation leads to pathologic thrombus formation and organ failure. The decisive central step for different processes of platelet activation is the increase in cytosolic Ca 2؉ activity ([Ca 2؉ ] i ). Activation-dependent depletion of intracellular Ca 2؉ stores triggers Ca 2؉ entry from the extracellular space. Stromal interaction molecule 1 (STIM1) has been identified as a Ca 2؉ sensor that regulates store-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 50 publications
(80 reference statements)
2
78
0
Order By: Relevance
“…Thus, our results provide a new potential mediator, STIM1, in those signaling pathways where MAPK and Ca 2+ entry are involved. This would be the case for platelet activation (Elvers et al, 2012) and myoblast differentiation (Lee et al, 2012), although the hypothesis has not been fully confirmed in those cell types due to the lack of phosphospecific antibodies against those sites. Because our work has focused on the molecular mechanism underlying the regulation of STIM1 activity by phosphorylation, the involvement of STIM1 phosphorylation in signaling pathways and physiological events mediated by ERK1/2 will require further study in the future.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, our results provide a new potential mediator, STIM1, in those signaling pathways where MAPK and Ca 2+ entry are involved. This would be the case for platelet activation (Elvers et al, 2012) and myoblast differentiation (Lee et al, 2012), although the hypothesis has not been fully confirmed in those cell types due to the lack of phosphospecific antibodies against those sites. Because our work has focused on the molecular mechanism underlying the regulation of STIM1 activity by phosphorylation, the involvement of STIM1 phosphorylation in signaling pathways and physiological events mediated by ERK1/2 will require further study in the future.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to HEK293 cells, STIM1 phosphorylation, detected by an anti-phospho-MAPK/CDK substrate antibody, is enhanced by thapsigargin in neonatal rat ventricular myocytes (Zhu-Mauldin et al, 2012). Moreover, it has been reported that STIM1 phosphorylation at Ser575 promotes C2C12 myoblasts differentiation to myocytes (Lee et al, 2012), and that Ser to Ala mutation of residues 575, 608, and 621 impairs platelet adhesion to fibrinogen (Elvers et al, 2012), further supporting a role for STIM1 phosphorylation in cell physiology.…”
mentioning
confidence: 89%
“…CyPA plays an important role as a Ca 2+ regulator in platelets. 150 Moreover, extracellular CyPA activates platelets via basigin (CD147)-mediated phosphoinositide-3-kinase/Akt signaling, leading to enhanced adhesion and thrombus formation. 151,152 Moreover, thrombin suppresses eNOS in EC via Rho-kinase pathway.…”
Section: Rho-kinase-mediated Development Of Cardiovascular Diseasesmentioning
confidence: 99%
“…Furthermore, CypA-PPIase facilitates ubiquitination of CXCR7 translocating it to the platelet surface (31). CypA is also involved in influencing thrombosis and haemostasis functions of platelets as elaborated in CypA -/-mice (37,38). CypA functions as a critical calcium sensor and regulator for store release and refill as mediated by Orai1 (38).…”
Section: Macrophage Migration Inhibitory Factor (Mif)mentioning
confidence: 99%
“…CypA is also involved in influencing thrombosis and haemostasis functions of platelets as elaborated in CypA -/-mice (37,38). CypA functions as a critical calcium sensor and regulator for store release and refill as mediated by Orai1 (38). CypA-dependent increase in ROS production leads to inside-out signalling causing increased GPIIb/IIIa activation and enhanced binding to fibrinogen.…”
Section: Macrophage Migration Inhibitory Factor (Mif)mentioning
confidence: 99%